2014
DOI: 10.1007/s13181-014-0401-8
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Simulation-Based Education Versus Lecture-Based Instruction for Toxicology Training in Emergency Medicine Residents

Abstract: Simulation-based teaching (SIM) is a common method for medical education. SIM exposes residents to uncommon scenarios that require critical, timely actions. SIM may be a valuable training method for critically ill poisoned patients whose diagnosis and treatment depend on key clinical findings. Our objective was to compare medical simulation (SIM) to traditional lecture-based instruction (LEC) for training emergency medicine (EM) residents in the acute management of critically ill poisoned patients. EM resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Simulation incorporates communication, teamwork, hands-on practice, and standardized assessments of patient care scenarios without risking patient injury or discomfort. Multiple studies comparing high-fidelity simulation training to standard lectures have found simulation improves long-term knowledge retention, 1 performance…”
mentioning
confidence: 99%
“…Simulation incorporates communication, teamwork, hands-on practice, and standardized assessments of patient care scenarios without risking patient injury or discomfort. Multiple studies comparing high-fidelity simulation training to standard lectures have found simulation improves long-term knowledge retention, 1 performance…”
mentioning
confidence: 99%
“…To assess effective learning and long‐lasting retention, a 20 multiple‐choice‐question questionnaire on positive inotropic drugs was administered at several time intervals: at baseline, after lecture, immediately after simulation (either Sham or LF or HF) and 3 months after simulation to obtain information on long‐lasting retention, as previously suggested . A 20‐minute period was allowed to complete the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, studies show that when training medical students on proper critical assessment and management of critically ill patients, students trained via an SBME method outperform students trained via a didactic lecture or problem-based learning method [38,39]. SBME has also been shown to enhance retention of training information compared to lectures [40]. While changing all aspects of medical curricula is important for preparing students to address the heroin and fentanyl crisis, simulation is a necessary component to ensure students are as best prepared as possible.…”
Section: Simulation-based Training: Opioids and Heroinmentioning
confidence: 99%